2022
DOI: 10.1159/000524361
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Universal Cervical Length Screening Program in a Large Hospital System: It Takes Some Time to Achieve Consistent Results

Abstract: Objective: To describe changes in the acceptance of transvaginal (TV) cervical length (CL) measurements, and in the variance of CL measurements among operators, after implementation of universal TV-CL measurements at 18+0-23+6 weeks/days of gestation. Study Design: Retrospective cohort study Participants/Materials, Setting, Methods This study was performed after universal TV-CL screening was implemented at the University of Texas Health Science Center in Houston, Texas, for all women undergoing an anatomy u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Current clinical standards that identify women at high risk of PTB include cervical length assessment and screening for fetal fibronectin, a protein elevated in the vaginal pool near birth . However, these approaches are inadequate and often inconclusive in predicting the complex phenotype of PTB. , Despite advances in biomarker discovery, prediction of the onset of PTB has remained a challenge because (1) current clinical assays have poor sensitivity and specificity which fail to identify relevant biomarkers; (2) single biomarker tests are ineffective due to low positive predictive values; (3) there are significant inter- and intra-assay disparities due to variations in the detection method, sample type used, and timing of sample collection which make comparative analysis of biomarkers difficult for PTB prediction; and (4) while some studies have reported multiplexed screening using the same sample type and platform, there were significant variations in the study designs and clear conclusions could not be drawn. An unmet clinical need exists for an effective screening tool that enables quantitative detection of unconventional biomarkers of PTB with high sensitivity and specificity at clinically relevant levels, yet simultaneously be low-cost allowing early, accurate, and affordable screening for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Current clinical standards that identify women at high risk of PTB include cervical length assessment and screening for fetal fibronectin, a protein elevated in the vaginal pool near birth . However, these approaches are inadequate and often inconclusive in predicting the complex phenotype of PTB. , Despite advances in biomarker discovery, prediction of the onset of PTB has remained a challenge because (1) current clinical assays have poor sensitivity and specificity which fail to identify relevant biomarkers; (2) single biomarker tests are ineffective due to low positive predictive values; (3) there are significant inter- and intra-assay disparities due to variations in the detection method, sample type used, and timing of sample collection which make comparative analysis of biomarkers difficult for PTB prediction; and (4) while some studies have reported multiplexed screening using the same sample type and platform, there were significant variations in the study designs and clear conclusions could not be drawn. An unmet clinical need exists for an effective screening tool that enables quantitative detection of unconventional biomarkers of PTB with high sensitivity and specificity at clinically relevant levels, yet simultaneously be low-cost allowing early, accurate, and affordable screening for patients.…”
Section: Introductionmentioning
confidence: 99%
“…5 Until recently, only a few studies assessed the sonographer's performance in obtaining TVCL images. Soto et al 24 In a prospective cohort study, Joly et al 25 evaluated 10 resident physicians who acquired five images of the cervix before and after completion of the theoretical course and images audit using a maximum score of 8 over the eight criteria suggested by CLEAR. 10 The overall performance was improved after obtaining the certification (mean score of 6.6 ± 0.9 vs 4.3 ± 2.1; P < 0.001) immediately after the training.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, only a few studies assessed the sonographer's performance in obtaining TVCL images. Soto et al 24 evaluated the changes over time after the implementation of TVCL screening in the success rate for performing TVCL scans according to the experience of the certified operators. The authors found that less experienced sonographers had a lower rate of TVCL scans (80.8% [56.4%–92.3%]) than those with more than 10 years of experience (85.8% [62.3%–97.2%]; P = 0.03) and that most, but not all, sonographers improved their success rate for obtaining TVCL measurements after the first 6 months after the introduction of universal TVCL screening.…”
Section: Discussionmentioning
confidence: 99%
“…Note: none of these current clinical measures alone is predictive of PTL risk. [5][6][7] Finally, we wanted to compare Raman findings with clinical assays of protein biomarkers that are standard practice for prediction of PTL but have not been reliable measure of PTL diagnosis in 1 st trimester. Here we performed enzyme linked immunosorbent assay (ELISA)…”
Section: Resultsmentioning
confidence: 99%
“…4 The effectiveness of these tools is also inconclusive based on previous studies. [5][6][7] Patient history such as previous preterm births and miscarriages have in a strong correlation to PTL, but this is irrelevant for women experiencing their first pregnancy. 8 To diagnose and find appropriate solutions with sufficient time for treatment, a forecasting tool would ideally be able to take data from the first trimester and predict the likelihood of a mother developing PTL, with or without previous preterm births or miscarriage data.…”
Section: Introductionmentioning
confidence: 99%